The Effect Of Dictogloss Technique Toward Students’ Writing Mastery On Narrative Text At The Second Grade Students Of Senior High School Pandeglang 11 - Sely Fujianti; Ade Sudirman (Universitas Mathla'ul Anwar Banten, 2019)
This research aims to investigate the effect of Dictogloss Technique as learning media to improve students’ narrative writing at the second grade students of SMA 11 Pandeglang. The researcher paper employs the quantitative research design with the quasi experiment. It used test to collect the data involving observation pre-test and post-test. The observation is conducted before the research was done. The researcher asked to the teacher and students about teaching learning process in the class. The pre-test is conducted to know their basic writingmastery. And the post-test conducted after the treatment. The data analysis is conducted to identify important finding as it is expected by the objective of the research.Based on the results of research and analysis of the data, obtained mean of post-test score in the experiment class was 72,89and the control class was 43,58. It shows that there are significant differences from the results obtained both of classes. The results of hypothesis testing by using Mann-Whitney found that on degree of significance 5% ( α= 0.5) two-tailed was 0,00 was α= 0,05 or two-tailed< α= 0.5 (0,00<0,05) it means was rejected and was accepted.The findings reveal that the effect of Dictogloss Technique is helpful and easy to conduct. In addition, this media can improve students’ narrative writing. In relations to the students response on the media, found that students response the media positively. Moreover, they feel happy and enthusiastic to practice this media in narrative writing mastery.Based on finding of research, it is significant for the teacher to choose the appropriate media for improving students’ narrative writing mastery, particularly Dictogloss Technique as mentioned above.